Studies on the Functionality of Newly Synthesized Fibrinogen after Treatment of Acute Myocardial Infarction with Streptokinase, Increase in the Rate of Fibrinopeptide Release - Regano, Edelmiro; Vila, Virtudes; Aznar, Justo; Lacueva, Victoria; Martinez, Vicenta; Ruano, Miguel (Thrombosis and Haemostasis, 1993)
In 15 patients with acute myocardial infarction who received 1,500,000 U of streptokinase, the gradual appearance of newly synthesized fibrinogen and the fibrinopeptide release during the first 35 h after SK treatment were evaluated. At 5 h the fibrinogen circulating in plasma was observed as the high molecular weight fraction (HMW-Fg). The concentration of HMW-Fg increased continuously, and at 20 h reached values higher than those obtained from normal plasma. HMW-Fg represented about 95% of the total fibrinogen during the first 35 h. The degree of phosphorylation of patient fibrinogen increased from 30% before treatment to 65% during the first 5 h, and then slowly declined to 50% at 35 h.The early rates of fibrinopeptide A (FPA) and phosphorylated fibrinopeptide A (FPAp) release are higher in patient fibrinogen than in isolated normal HMW-Fg and normal fibrinogen after thrombin addition. The early rate of fibrinopeptide B (FPB) release is the same for the three fibrinogen groups. However, the late rate of FPB release is higher in patient fibrinogen than in normal HMW-Fg and normal fibrinogen. Therefore, the newly synthesized fibrinogen clots faster than fibrinogen in the normal steady state.In two of the 15 patients who had occluded coronary arteries after SK treatment the HMW-Fg and FPAp levels increased as compared with the 13 patients who had patent coronary arteries.These results provide some support for the idea that an increased synthesis of fibrinogen in circulation may result in a procoagulant tendency. If this is so, the HMW-Fg and FPAp content may serve as a risk index for thrombosis.